INOVASI PACKAGING DAN LABELING PADA PRODUK UMKM JAMUR CRISPY DI DESA SUKOYOSO, KECAMATAN SUKOHARJO, KABUPATEN PRINGSEWU - Nasyi’atun Inayati Utami; Dewi Mariam Widiniarsih; Dhea Eka Putri; Wagiyo (MUHKAL, 2023)
Community service activities (PKM), carried out in villages in need, namely Sukoyoso, Sukoharjo, Pringsewu. This activity is a collaboration between students guided by lecturers with Micro, Small and Medium Enterprises (MSMEs) partners. Oyster Mushroom MSMEs produce various processed mushrooms such as Crispy Mushrooms where these preparations have been circulating in the market. But it is not yet a high quality bar product. This PKM activity aims to optimize a more unique processed taste so that it has a high selling value through product packaging and labeling innovations, as well as expanding product marketing through online marketing assistance for MSMEs. The team uses methods that will be implemented during the activity by sharing and assisting partners in innovating. The planned output is the increase in product sales from the innovation of packaging and product labeling, as well as the expansion of the product market through online marketing.